BAS-RELIEF IMAGES ON THE DOLMEN OF THE KAPIBGE-1 GROUP IN THE VICINITY OF GREATER SOCHI - Glazov, Konstantin Anatol'evic; Kudin, Mihail Ivanovic; Kizilov, Andrej Sergeevic (History, Archeology and Ethnography of the Caucasus, 2024)
The article presents the results of a study of a complex of bas-relief images found on the dolmen of the Kapibge-1 group, located in the vicinity of the Mizegukh ridge on the northern outskirts of Greater Sochi. The purpose of this work is to introduce into scientific circulation a story bas-relief unique to the Western Caucasus, depicted on the facade of a dolmen that is not included in the register of the regional department of state protection of cultural heritage objects. The images are made in bas-relief technique with background picketing and represent a doe with a cub, chased by a dog, two hunters with bows, three pairs of anthropomorphic figures and five bird-like images. As a result of the analysis of well-known images in the ancient cultures of the Caucasus and Crimea, the possibility of the bas-relief belonging to the dolmen culture is substantiated. The study of the images was carried out using photogrammetry followed by 3D processing, which allows us to develop a technique for studying petroglyphs and bas-reliefs using a shadow pattern formed by virtual light sources. Using the example of this monument, some post-processing techniques of the final 3D model were tested, based on the use of virtual materials with different optical properties to select the desired shadow and glare pattern, as well as gradient procedural maps, which allowed the bas-relief images to be clearer and their poorly preserved fragments to be revealed. The bas-relief images were discovered during the monitoring of archaeological sites of the historical and cultural heritage of the Black Sea coast of the Caucasus at a selective polygon – the territory of Greater Sochi. The monitoring objectives are to compile a register and catalog of archaeological sites and the subsequent development of technologies for their conservation and use, as well as to prevent the loss of historical and cultural heritage sites in recreational potential development zones.